Anatomical and physical properties of three lesser-known timber species from Malaysia - Abdullah Siam, Nordahlia; Lipeh, Shahlinney; Uyup, Mohd Khairun Anwar; Ahmad Juhari, Muhammad Amirul Aiman; Talip, Noraini; Che Amri, Che Nurul Aini; Abdullah, Nor Azahana (North Carolina State University, 2022)
The purpose of this study was to determine the anatomical and physical properties of three lesser-known Malaysian timber species, i.e., mahang (Macaranga hosei), medang (Litsea costalis), and terap (Artocarpus scortechinii). Correlation factors that influenced the density and shrinkage were also discussed. From the results obtained, terap wood had the longest fibre (1421 µm), followed by medang (1309 µm), and mahang (1161 µm). Terap, medang, and mahang were categorized as having very thin fibres. The density of terap, medang, and mahang had average values of 504 kg/m3, 485 kg/m3, and 474 kg/m3, respectively. In addition, terap wood also showed the highest tangential shrinkage (3.8%), followed by mahang (2.2%) and medang (1.5%) wood. This present study showed that the density was significantly influenced by the fibre length, fibre wall thickness, vessel diameter, and number of vessels. In addition, the shrinkage was highly correlated with the density. Based on the conducted research, mahang, medang, and terap show potential as alternative raw material to fulfill demand in wood-based industries.